Sosialisasi Pencegahan Stunting di Lembang Issong Kalua’ - Darnita Rante Giri; Jelwanti Sombolayuk; Novita Pali’; Yoga Triputra Senolinggi; Stefani M. Palimbong (Pusat Riset dan Inovasi Nasional, 2022)
Stunting is a short toddler usually defined as failure to grow in babies and toddlers aged 0-59 months due to chronic malnutrition. on low growth and the cumulative effects of insufficient intake of energy and macronutrients in the long term. in South Sulawesi province in 2021, with an increase in stunting (34.1%). North Toraja is ranked 4th with the highes stunting prevalence . Lembang Issong Kalua' cases of stunting in toddlers consist of 13 children and 6 pregnant women. Implementation method using a quantitative case study approach by collecting data on toddlers and pregnant women to add education about providing additional food for toddlers and pregnant women. discussion result: provision of additional food, distribution of vitamins, counseling on nutritional problems. Preparing food supplies is for measuring food for toddlers and pregnant women. Providing additional food, the stunting rate among toddlers has reduced to only around 13 toddlers to 5 toddlers who are still monitoring the growth of toddlers. Lack of public understanding about stunting and nutritional needs is a socio-economic problem in the community.